THE PROGNOSTIC IMPORTANCE OF RISK FACTORS AND MEDICAL HISTORY DATA ON THE MORTALITY OF PATIENTS OF STABLE ANGINA AT 5 YEARS PROSPECTIVE STUDY (FRAGMENT OF THE REGISTER ACS/AMI - R. S. Mamutov; D. A. Mamaradjapova (Евразийский Кардиологический Журнал)
Aim: Studying of outcomes of stable angina during five years' prospective study according to the Register of an acute coronary syndrome and an acute myocardial infarction (ACS/AMI) with an assessment of the prognostic importance of risk factors and medical history data on mortality.Material and Methods: In this paper we studied the results of 5-year prospective study of 196 patients suffering from stable angina, with the assessment of the impact of risk factors and medical history data on mortality from stable angina according to register ACS / AMI.Results. The most common risk factor for CHD among hospitalized patients with stable angina, hypertension was (80.6%) and GC (39.3%). Prior to admission in more than % patients had angina before, more than 2/5 suffered MI earlier, there were У signs of CHF, У suffered from diabetes. During the period of the five-year prospective study of 196 patients with stable angina in 54 patients (29.6%) developed acute myocardial infarction and of which 24% was observed in death. Five-year mortality in patients with stable angina - 23.5%, with the main cause of death (63%) were acute heart failure. For 5 years of prospective study, the presence of heart failure and diabetes, and patients with a history of myocardial infarction is associated with a poor prognosis for mortality with stable angina.